Study of Solvent Variation on Sustainable Synthesis of Nanostructured FeCo2O4 by Chemical Bath Deposition Method - Payal S. Ghorpade,; Popat S. Tambade,; Swapnil R. Bankar, (International Journal of Scientific Research in Science and Technology, 2025)
The present investigation deals with controlled synthesis of nanostructured FeCo2O4 thin film by simple and economical chemical bath deposition (CBD) technique directly on glass plate substrate, without adding surfactant or binders. The consequences of different compositions of solvents on morphological properties have been studied systematically. Herein we used different solvent compositions as double distilled water (DDW), pure ethanol and distilled water: ethanol (1:1). The morphologies of nanostructured thin film of FeCo2O4 modify substantially with change in a solvent. The fabricated nanofilm were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray Diffractometer (XRD) analysis and Field Emission - Scanning Electron Microscopy (FE-SEM).So our work may provide a new approach of solvent effect to obtain thin film by chemical bath deposition method.
Keywords: FeCo2O4; thin film; solvent; Chemical bath deposition (CBD)